Features of the course of diabetes mellitus in IgG4-associated disease - T. S. Panevin; A. V. Torgashina; A. A. Movsesyan (Сахарный диабет)
IgG4-related disease (IgG4-RD) is characterized by the appearance of tumor-like foci in one or more organs, occurring synchronously or metachronously, due to fibro-inflammatory changes with hypersecretion of immunoglobulin G subclass 4 (IgG4) in tissues and/or blood serum. Diabetes mellitus (DM) develops among 43-68% of patients with IgG4-related pancreatitis. Diabetes against the background of IgG4-RD can be caused both by damage to the endocrine part of the pancreas and the use of glucocorticosteroids, but its course is moderate, with a rare need for insulin therapy. In both cases, the use of genetically engineered biological therapy with rituximab may be accompanied by an improvement in carbohydrate metabolism. This article describes the course of diabetes and the need for hypoglycemic therapy for 1.5 years in a patient treated with IgG4-RD.